Fabrication of flexible, transparent and conductive films from single-walled carbon nanotubes with high aspect ratio using poly((furfuryl methacrylate)-co-(2-(dimethylamino)ethyl methacrylate)) as a new polymeric dispersant. Issue 15 (21st April 2015) - Lee, Taeheon; Kim, Byunghee; Kim, Sumin; Han, Jong Hun; Jeon, Heung Bae; Lee, Young Sil; Paik, Hyun-jong
<x xml:space="preserve">Abstract</x> We synthesized p(FMA-co-DMAEMA) for the dispersion of SWCNTs while maintaining their high aspect ratios.